The Atopic Dermatitis Control Tool: Adaptation and Content Validation for Children and Caregivers of Children with Atopic Dermatitis - Chien-Chia Chuang; David M. Pariser; Eric Simpson; Jennifer Dine; Michelle Brown; Sheri Fehnel; Zhixiao Wang (Adis, Springer Healthcare, 2024)
Abstract Introduction The Atopic Dermatitis Control Tool (ADCT) assesses six concepts regarding patient-perceived control of atopic dermatitis (AD) in adults and adolescents with AD. This study aimed to develop two modified ADCT versions, one for children with AD aged 8-11 years and another for caregivers of children with AD aged 6 months to 11 years. Methods Following the US Food and Drug Administration patient-reported outcomes guidance, the ADCT was modified to produce draft Child and Caregiver ADCT versions, maintaining the original six concepts. The instruments were refined and finalized through an iterative process using input from children with AD and caregivers of children with AD via qualitative interviews. Inclusion criteria were clinician diagnosis of AD, prescription treatment use in the past 3 months, and itching/scratching or rash in the past month. Interviews consisted of concept elicitation to identify perceptions of AD control and cognitive debriefing to test and refine the ADCT items. Results In total, 19 children (mean age 9.2 years, 74% male) and 17 caregivers (mean age 36.3 years, 100% female) were interviewed. During concept elicitation, children and caregivers reported similar symptoms and described the cycling and unpredictability of AD. Most participants reported that daily activities were impacted negatively by AD symptoms. The concept of AD control resonated with children and caregivers, and respondents were able to describe their experiences related to AD symptom severity. Children were unfamiliar with the term AD, so the Child ADCT version was named the Child Eczema Control Tool (ECT). Children and caregivers both reported that the instruments assessed relevant concepts, comprehensively measured AD control, and demonstrated content and face validity. Conclusions The Child ECT and Caregiver ADCT were developed and qualitatively validated for assessing AD control in patients aged 6 months to 11 years and may offer simple ways to assess disease control and optimize treatment decisions. Video Abstract